Research of methods of antibacterial treatment of textile materials - Nazarova, Matluba (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this article, analyzes were conducted on the basis of the types, characteristics, processing processes, areas of use, advantages, disadvantages of the new structural antibacterial, hygienically usable gauzes created on the basis of modern innovative technologies.